Optimization of heat removal and radiation protection of dry cask storage for MTR spent nuclear fuel. (15th June 2023) - Istavara, A.; Ratiko, R.; Aziz, M.; Aisyah, A.; Nasruddin, N.
Highlights: The limited wet-type storage space for Indonesia's SNF requires study on dry cask storage. The dry storage study is performed by considering the safety factors (criticality, radiation protection, and heat removal) and cost. The safety-, cost- and multi-objective optimization results were validated experimentally. This study can be developed to other types of dry storage design by changing the decision variable values. Abstract: To provide a solution for the limited storage space in wet-type storage in Indonesia's material testing reactor (MTR) spent nuclear fuel (SNF) storage, a study on dry cask storage for MTR SNF is needed. This study designed, simulated, and experimentally calculated the safety parameters and the manufacturing cost of dry cask storage simultaneously. The optimization results were validated and analyzed using experimental data from a dry cask storage prototype. Decision variables and constraints were provided as inputs into the MATLAB software to obtain three optimized conditions: safety, cost, and multi-objective optimized conditions. The multi-objective optimization results demonstrated that the thickness of dry storage design concrete and lead (Pb) are 0.06 and 0.51 m, respectively. The height and width of the vent are 0.15 and 0.5 m, respectively, and the vent elevation difference is 2.43 m. For five variables, the optimum value for the canister surface temperature is 66.8 °C and the cost required to manufacture this dry storage is USD 147, 827. Moreover, MicroShield validation revealed that the dry cask storage surface exposure is 104.8 mR/h, which is lower than the safe limit of the maximum value specified as 160 mR/h. The simulation of the canister surface temperature using ANSYS Fluent showed that the surface temperature value is close to the calculations performed in MATLAB. Temperature validation of experimental data from the dry storage prototype indicated that the temperature obtained via theoretical and experimental calculations is relatively close: 45.2 and 51.3 °C. This research can be developed to other types of dry storage design by changing the value of the decision variables that is appropriate for the dry storage type to be designed.